2021
DOI: 10.1371/journal.pone.0245886
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on mobility in ten countries and associated perceived risk for all transport modes

Abstract: The restrictive measures implemented in response to the COVID-19 pandemic have triggered sudden massive changes to travel behaviors of people all around the world. This study examines the individual mobility patterns for all transport modes (walk, bicycle, motorcycle, car driven alone, car driven in company, bus, subway, tram, train, airplane) before and during the restrictions adopted in ten countries on six continents: Australia, Brazil, China, Ghana, India, Iran, Italy, Norway, South Africa and the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(119 citation statements)
references
References 78 publications
6
98
0
5
Order By: Relevance
“…On the other hand, trip frequency before the COVID-19 outbreak has a negative impact on the choice to cancel the journey [23,29,46] for both students and workers. As regards the effects of COVID-19 on educational and working trips, health risk perception plays a fundamental role in trip cancellation decisions [19], in particular for public transport modes [24,65]. This points out that a proper information campaign on the use of such means can significantly impact future travel demand [4,7,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, trip frequency before the COVID-19 outbreak has a negative impact on the choice to cancel the journey [23,29,46] for both students and workers. As regards the effects of COVID-19 on educational and working trips, health risk perception plays a fundamental role in trip cancellation decisions [19], in particular for public transport modes [24,65]. This points out that a proper information campaign on the use of such means can significantly impact future travel demand [4,7,31].…”
Section: Discussionmentioning
confidence: 99%
“…Countermeasures against the diffusion of COVID-19 had a significant impact on mobility [1,12,13,19] because of direct limitations or bans on transport services, forbidden trips, the closure of activities, as well as self-imposed individual restrictions [20]. Many authors reported significant changes in users' travel habits worldwide [7,8,21,22], with variations in the frequency of trips, travel purposes and modal split [12], which may have varied in accordance with country-specific factors [23,24] and socio-economic characteristics of citizens [25]. As regards European nations, comparing trip statistics before and after the pandemic: in Germany, about 60% of persons changed transport mode [14], in particular, the number of people performing monomodal trips rose from 68% to 83% [26]; in Greece, the average number of daily trips decreased by 50% [12]; in the Netherlands, about 80% of people reduced their out-of-home activities and the number of trips decreased by 55% compared to 2019 [9]; in Poland, 50% of people reduced their travel time by more than two thirds [20]; commuting trips dropped by 80% in Spain [13]; in Italy, the number of people reporting no daily trips increased by 27% [24] and the number of internal trips decreased by 50% [27,28], while commuting trips were reduced by 69% [8]; even in Sweden, where restrictions were voluntary, 86% of the population changed their commuting trips with 66% of people who commuted for 5 days a week prior to the pandemic deciding not to travel [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Facilitated by globalisation and our hypermobile society (Acter et al 2020 ; SanJuan-Reyaes et al 2020 ; Sarkar et al 2020 ), the COVID-19 pandemic has become another grave issue for humanity as a whole, forcing radical changes in many social, economic and hygienic behaviours (WHO 2020a , b ; Passavanti et al 2021 ; Wu 2021 ). In order to curb the spread of the COVID-19 virus, a significant amount of the global population has been requested to comply with restrictions to economic and mobility activities (De Vos 2020 ; Wilder-Smith and Freedman 2020 ; Barbieri et al 2021 ). Although essential industries have been operating continuously (Wang et al 2020a b ), the massive decline in the global pattern of energy demand (i.e.…”
Section: Introductionmentioning
confidence: 99%